FEMININE SENSIBILITY IN CHITRA BANERJEE DIVAKARUNI’S SISTER OF MY HEART - L.A, Jhansy Anitha.; Saravanan, K. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In Chitra Banerjee Divakaruni’s novel Sister of My Heart, the exploration of feminine sensibility through the lives of Anju and Sudha unveils a compelling narrative of resilience, struggle, and self-discovery in the face of societal pressures and male dominance in India. As the protagonists navigate the complexities of patriarchal society, their experiences shed light on the psychological impacts of entrenched gender norms and the challenges of carving out individual identities within a rigidly defined feminine role. Divakaruni skillfully contrasts Indian and American notions of feminism, delving into how cultural and sociological differences shape feminine sensibility and influence familial and marital relationships – underscoring the emotional toll wrought by societal, cultural, and psychological pressures on women. Through an examination of Anju and Sudha’s journeys, this research paper aims to delve deeper into the multifaceted nature of feminine roles and identities, offering insights into the intricate interplay between personal agency and external constraints in shaping women’s lived experiences.